Method for producing Al4SiC4 composition

By using activated carbon in the calcination process of aluminum, silicon, and carbon sources, the method produces Al4SiC4 compositions with a sponge-like structure, addressing the challenges of particle sintering and adhesion, and achieving easy removal and reduced energy consumption.

JP7667666B2Active Publication Date: 2025-04-23TYK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2021035974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-08
Publication Date
2025-04-23
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Traditional methods for producing Al4SiC4 compositions result in particle sintering and adhesion to the crucible, making it difficult to remove the composition from the crucible and requiring excessive energy for grinding.

Method used

The method involves mixing aluminum, silicon, and carbon sources, including activated carbon, and calcining them in an inert gas atmosphere to produce Al4SiC4 compositions with a sponge-like structure, facilitating easy removal from the crucible.

Benefits of technology

The approach results in Al4SiC4 compositions with low relative density and excellent disintegration properties, allowing for easy removal from the crucible and reducing energy consumption in the grinding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667666000002
    Figure 0007667666000002
  • Figure 0007667666000003
    Figure 0007667666000003
  • Figure 0007667666000001
    Figure 0007667666000001
Patent Text Reader

Abstract

To provide a method of producing an Al4SiC4 composition, capable of easily extracting an Al4SiC4 composition out of a crucible.SOLUTION: The method of producing an Al4SiC4 composition by mixing raw materials each including an aluminum source, a silicon source, and a carbon source, filling a crucible with the mixture of the raw materials, and calcining the same in an inert gas atmosphere, in which activated carbon is added thereinto as at least a portion of the carbon source.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an Al4SiC4 composition. By law Regarding. [Background technology]

[0002] The Al4SiC4 (aluminum silicon carbide) composition is a carbide made of aluminum and silicon. In recent years, the Al4SiC4 composition has been attracting attention as a new functional additive for carbon-containing refractories. The effect of adding the Al4SiC4 composition is said to be the densification of the refractory structure. It is presumed that the densification of the refractory structure occurs when the Al4SiC4 composition present in the refractory structure reacts with CO gas in the atmosphere. That is, as shown in formula (1), it is presumed that this is brought about by the generation of gas containing Al from the Al4SiC4 composition at high temperatures, diffusing into the voids in the refractory structure, reacting with CO gas and condensing again as Al2O3 and carbon, filling the voids. Al4SiC4+6CO→2Al2O3+SiC+9C (1)

[0003] As a method for producing an Al4SiC4 composition, Non-Patent Document 1 discloses a method for producing an Al4SiC4 composition by mixing raw materials including an aluminum source, a silicon source, and a carbon source, loading the mixed raw materials into a crucible, and firing the mixture. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Journal of the Ceramic Society of Japan 103 [1] 20-24 (1995) Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the conventional method for producing an Al4SiC4 composition, there is a problem that at least a part of the Al4SiC4 particles synthesized in the crucible may solidify (sintering of the Al4SiC4 particles may occur). The solidification of the Al4SiC4 particles occurring in the crucible occurs not only between the particles but also between the Al4SiC4 particles and the inner wall surface of the crucible. If the particles present on the surface of the Al4SiC4 composition during synthesis are in contact with the inner wall surface of the crucible when synthesis is completed, the side of the solidified Al4SiC4 composition and the inner wall of the crucible will adhere to each other. The Al4SiC4 composition adhered to the inner wall of the crucible cannot be removed from the crucible even if the crucible is turned upside down.

[0006] In the conventional method for producing an Al4SiC4 composition, in order to take out the Al4SiC4 composition from the crucible, a process of crushing (breaking into pieces of a suitable size) the solidified Al4SiC4 composition in the crucible must be carried out in advance. Furthermore, if the Al4SiC4 composition taken out of the crucible is solidified, it is considered that the process of grinding it consumes more energy than necessary, and the crushing and grinding processes to make the Al4SiC4 composition usable as a raw material require a lot of energy and labor.

[0007] The present invention has been made in consideration of the above problems, and provides a method for producing an Al4SiC4 composition that allows the Al4SiC4 composition to be easily removed from a crucible. Law The purpose is to provide. [Means for solving the problem]

[0008] In order to solve the above problems, Ming is A method for producing an Al4SiC4 composition by mixing raw materials including an aluminum source, a silicon source, and a carbon source, loading the mixed raw materials into a crucible, and firing the mixture in an inert gas atmosphere, comprising: One Activated carbon is added as part The amount of the activated carbon added is 0.5 mass% to 40 mass% of the carbon source. The present invention relates to a method for producing an Al4SiC4 composition. Effect of the Invention

[0010] According to the present invention, by utilizing the shape characteristics of activated carbon, an Al4SiC4 composition having a low relative density (bulk density) and excellent crushability can be synthesized in a crucible. Therefore, the Al4SiC4 composition can be easily taken out from the crucible. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a process diagram of a method for producing an Al4SiC4 composition according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a graph showing the effect of the amount of activated carbon added on the crushability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, a method for producing an Al4SiC4 composition according to an embodiment of the present invention will be described in detail with reference to the accompanying drawings. However, the present invention can be embodied in various forms and is not limited to the embodiments described in the present specification. The present embodiment is provided with the intention of enabling a person skilled in the art to fully understand the invention by fully disclosing the specification. (Manufacturing method)

[0013] As shown in FIG. 1, the method for producing an Al4SiC4 composition of the present embodiment uses an aluminum source, a silicon source, and a carbon source as starting materials (S1).

[0014] The aluminum source may be metal Al, aluminum oxide, aluminum hydroxide, etc. From the standpoint of purity and production efficiency, it is preferable to use metal Al powder.

[0015] The silicon source can be metal Si or silicon dioxide. Metal Si powder is preferable from the viewpoint of purity and production efficiency. Al-Si alloy powder can also be used as the aluminum source and silicon source.

[0016] Activated carbon is used as at least a part of the carbon source. That is, the carbon source is composed of a first carbon source such as scaly graphite or carbon black, and activated carbon (second carbon source) added to the first carbon source. The entire amount of the carbon source may be activated carbon.

[0017] Activated carbon is produced from fossil raw materials such as coal, petroleum pitch and tar, pulp materials, or waste materials generated during the manufacture of molasses, by subjecting the raw materials to an activation process to introduce fine pores into the carbonized particles. The activation process is carried out by heating the carbonized particles together with atmospheric gas or chemicals at high temperatures of about 500°C to 1000°C. When the volatile components generated from the carbonized particles or the carbon itself are gasified during heating, fine pores measuring up to about 100 Å in size develop inside the particles. The formation of a large number of fine pores inside the particles increases the specific surface area of ​​the particles to 1000 m. 2 It will grow to be larger than / g.

[0018] The large specific surface area of ​​activated carbon promotes reactivity during synthesis. The generation of many reaction sites generates a large amount of crystal nuclei of Al4SiC4 particles, and the Al4SiC4 particles grow uniformly from the large amount of crystal nuclei, making sintering difficult. This results in an Al4SiC4 composition that is difficult to solidify, easy to disintegrate, and has a uniform particle size. Since the Al4SiC4 composition is formed in a sponge-like shape, this effect will be referred to as the sponge effect below.

[0019] The activated carbon is added in an amount of 0.1 mass% to 100 mass% based on the amount of the carbon source. That is, 0.1 mass% to 100 mass% of the carbon source is activated carbon, and 0 mass% to 99.9 mass% is the first carbon source.

[0020] In this embodiment, the amount of activated carbon added is set to 0.1 mass% to 100 mass% based on the carbon source, based on the result of examining the effect of the amount of activated carbon added on the crushability of the Al4SiC4 composition. As shown in FIG. 2, when the amount of activated carbon added is 0 mass%, the Al4SiC4 particles are solidified and the sponge effect is not exhibited, so the crushability of the Al4SiC4 composition synthesized in the crucible is significantly poor (rank D). When the amount of activated carbon added is 0.1 mass% or more, the sponge effect is exhibited, so the crushability rank is improved by one rank to be good (rank C). When the amount of activated carbon added is 0.5 mass% or more, the Al4SiC4 particles remain solidified, but the sponge effect is superior to the solidification of the Al4SiC4 particles, so the crushability rank is improved by two ranks (rank B). When the amount of activated carbon added is 5 mass% or more and 20 mass% or less, the solidification of the Al4SiC4 particles hardly occurs and the sponge effect is maximized, so the crushability rank is improved by three ranks (rank A). If the amount of activated carbon added exceeds 40 mass%, the sponge effect increases, but the heat retention increases due to voids, which causes sintering, resulting in a lower crushability rank (ranks B and C). The optimal amount of activated carbon added is 0.1 mass% to 100 mass% (ranks A, B, and C), preferably 0.5 mass% to 40 mass% (ranks A and B), and more preferably 5 mass% to 20 mass% (rank A).

[0021] The aluminum source, silicon source, and carbon source are weighed in amounts such that the molar ratio of aluminum, silicon, and carbon contained therein is 4:1:4. Additives such as silicon carbide may be added to these, if necessary.

[0022] Next, the starting materials are mixed using a mixer such as a dry Henschel mixer (S2). The mixing time is not particularly limited, but it is preferable to mix for 5 minutes or more to thoroughly mix the materials.

[0023] Next, the resulting mixed material is loaded into a crucible (S3), such as a carbon crucible.

[0024] Next, the crucible is placed in a resistance heating furnace, a batch furnace such as a tubular furnace, or a continuous furnace such as a tunnel furnace, and the mixed raw material is fired in an inert gas atmosphere (S4). The firing is carried out in an argon atmosphere at a temperature of 1650 to 1900°C for 1 to 10 hours. An Al4SiC4 composition is synthesized in the crucible by firing.

[0025] The synthesis of the Al4SiC4 composition is carried out in the following two stages. That is, as the temperature rises due to heating, Al4C3 and SiC are first produced as shown in formulas (2) and (3), and then Al4C3 and SiC react to produce Al4SiC4 at 1300°C or higher as shown in formula (4). At temperatures below 1650°C, Al4C3 is likely to remain after the reaction, while at temperatures above 1650°C, the rate of production of Al4SiC4 is significantly accelerated. Therefore, it is desirable to set the heating temperature to 1650°C or higher. 4Al+3C → Al4C3(2) Si+C→SiC (3) Al4C3+SiC→Al4SiC4(4)

[0026] After the synthesis of the Al4SiC4 composition, the crucible is removed from the furnace. Then, the crucible is turned over to remove the Al4SiC4 composition from the crucible (S5). When removing the Al4SiC4 composition from the crucible, the Al4SiC4 composition in the crucible does not need to be crushed, and may be crushed using a tool such as a hammer or a chisel. If the Al4SiC4 composition can be easily removed by simply turning the crucible over, the removal process can be automated using an industrial robot.

[0027] The Al4SiC4 composition taken out of the crucible may or may not be pulverized. For example, when the particle size of the Al4SiC4 composition is large to be used as a functional additive for carbon-containing refractories, the Al4SiC4 composition is pulverized with a pulverizer such as a roll crusher. Even when pulverized, the particle size of the Al4SiC4 composition is relatively uniform, so there is little loss in pulverization until the target particle size is reached. (Al4SiC4 composition)

[0028] The Al4SiC4 composition of the present invention has excellent crushability. This is specified by the ratio of the relative density of the Al4SiC4 composition to the theoretical density of Al4SiC4. That is, the relative density of the Al4SiC4 composition is 10% to 20% of the theoretical density of Al4SiC4. If the relative density is less than 10%, the Al4SiC4 composition cannot be maintained as a mass and becomes powdery, which causes a problem of environmental deterioration such as dust, whereas if it is 10% or more, this problem can be solved. If the relative density exceeds 20%, the Al4SiC4 particles solidify, which causes a problem of reduced crushability. The optimal relative density is 10% to 20%.

[0029] The relative density of the Al4SiC4 composition can be calculated by dividing the bulk density by the theoretical density. The bulk density can be calculated by measuring a certain volume of the synthesized Al4SiC4 composition. The theoretical density can be calculated by finding the volume from the unit cell of the Al4SiC4 crystal structure, finding the total mass of the atoms that make up the unit cell, and dividing the total mass by the volume. The theoretical density of Al4SiC4 is 3.03 g / cm 3 It is.

[0030] The method for measuring bulk density is specified in JIS R 1634 1998 (Method for measuring sintered density and open porosity of fine ceramics). Specifically, the Archimedes method was used for measuring bulk density, and a density / specific gravity measurement device (Mettler Toledo) was used. The above values ​​were used for the theoretical density, but theoretically, the theoretical density is equal to the true density, so the true density can also be taken as the theoretical density. The method for measuring true density is specified in JIS R 1620 1995 (Method for measuring particle density of fine ceramic powders). The pycnometer method was used for measuring true density, and an Accupyc II 1345 series device (Shimadzu Corporation) can be used.

[0031] In addition, the Al4SiC4 composition of the present invention has a relatively uniform particle size immediately after synthesis in an unground state, and the particle size distribution is also narrow. Specifically, the Al4SiC4 composition is crushed without a grinder, and the volume-based particle size distribution is measured. The particle size distribution span (D) is calculated by dividing the difference between the cumulative 90% particle size minus the cumulative 10% particle size by the cumulative 50% particle size. 90 -D 10 ) / D 50 is preferably 1.0 to 1.5, and more preferably 1.0 to 1.4. If the particle size distribution span is less than 1.0, the particle size distribution width is sharp and narrow, and a continuous particle size structure cannot be created, whereas if it is 1.0 or more, this problem can be solved. If the relative density exceeds 1.5, the particle size distribution has a broad base and a wide width. The optimal particle size distribution span is 1.0 to 1.5. If the particle size distribution span can be controlled to 1.0 to 1.5, it is advantageous to adjust the effect of adding the Al4SiC4 composition.

[0032] The volume-based cumulative 10% particle size, cumulative 50% particle size, and cumulative 90% particle size are measured by a laser diffraction scattering method. The method for measuring particle size distribution by the laser diffraction scattering method is standardized in JIS R 1629 1997. Specifically, a laser diffraction scattering particle size distribution measuring device MT3000II manufactured by Nikkiso Co., Ltd. was used, distilled water was used as the solvent, and the powder was ultrasonically dispersed in a sample circulator that was a standard accessory to the device, after which the particle size was measured. (Industrial Applicability)

[0033] The Al4SiC4 composition of the present embodiment can be used as a functional additive for improving the shape stability, strength and infiltration resistance of carbon-containing refractories. The Al4SiC4 powder of the present embodiment can be used not only as a functional additive for carbon-containing refractories, but also as an antioxidant, for example. EXAMPLES

[0034] Examples and Comparative Examples will be described below. In the Examples and Comparative Examples, the methods for measuring the various physical properties were as described above. Example 1

[0035] Metallic Al powder (-75 μm), metallic Si powder (-45 μm), carbon black (first carbon source, 60 to 280 nm), and activated carbon (second carbon source) were weighed out in a theoretical molar ratio of Al:Si:C = 4:1:4. The amount of carbon black added was 99.5 mass%, and the amount of activated carbon added was 0.5 mass%.

[0036] These raw materials were mixed for 10 minutes in a Henschel mixer. The mixed raw materials were loaded into a carbon crucible, and the carbon crucible was placed in a resistance heating furnace and sintered at 1800°C for 10 hours in an argon gas atmosphere. After sintering, the Al4SiC4 composition was taken out of the carbon crucible.

[0037] The resulting Al4SiC4 composition had a relative density of 17.1% and a bulk density of 0.52 g / cm 3 The particle size distribution span in the uncrushed state was 1.43. The crushability was good B (crushed into pieces when crushed by hand). Example 2

[0038] An Al4SiC4 composition was obtained in the same manner as in Example 1, except that the amount of carbon black added was 98.5 mass% and the amount of activated carbon added was 1.5 mass%.

[0039] The resulting Al4SiC4 composition had a relative density of 16.8% and a bulk density of 0.51 g / cm 3 The particle size distribution span in the uncrushed state was 1.41. The crushability was rated as good B (crushed into pieces when crushed by hand). Example 3

[0040] An Al4SiC4 composition was obtained in the same manner as in Example 1, except that the amount of carbon black added was 95 mass% and the amount of activated carbon added was 5 mass%.

[0041] The resulting Al4SiC4 composition had a relative density of 16.5% and a bulk density of 0.49 g / cm 3 The particle size distribution span in the uncrushed state was 1.32. The crushability was rated as good A (crushed into pieces without touching with hands). Example 4

[0042] An Al4SiC4 composition was obtained in the same manner as in Example 1, except that the amount of carbon black added was 80 mass% and the amount of activated carbon added was 20 mass%.

[0043] The resulting Al4SiC4 composition had a relative density of 13.5% and a bulk density of 0.41 g / cm 3 The particle size distribution span in the uncrushed state was 1.18. The crushability was rated as good A (crushed into pieces without touching with hands). Example 5

[0044] An Al4SiC4 composition was obtained in the same manner as in Example 1, except that the amount of carbon black added was 60 mass% and the amount of activated carbon added was 40 mass%.

[0045] The resulting Al4SiC4 composition had a relative density of 15.5% and a bulk density of 0.47 g / cm 3 The particle size distribution span in the uncrushed state was 1.28. The crushability was good B (crushed into pieces when crushed by hand). Example 6

[0046] An Al4SiC4 composition was obtained in the same manner as in Example 1, except that the amount of carbon black added was 0 mass% and the amount of activated carbon added was 100 mass%.

[0047] The resulting Al4SiC4 composition had a relative density of 18.1% and a bulk density of 0.55 g / cm 3 The particle size distribution span in the unground state was 1.32. The crushability was good C (crushed into pieces when lightly hit). Comparative Example 1

[0048] Metallic Al powder (-75 μm), metallic Si powder (-45 μm), and carbon black (60 to 280 nm) were weighed out in a theoretical molar ratio of Al:Si:C = 4:1:4. The amount of carbon black added was 100 mass%, and no activated carbon was added.

[0049] These raw materials were mixed for 10 minutes in a Henschel mixer. The mixed raw materials were loaded into a carbon crucible, and the carbon crucible was placed in a resistance heating furnace and sintered at 1800°C for 10 hours in an argon gas atmosphere. After sintering, the Al4SiC4 composition was taken out of the carbon crucible.

[0050] The resulting Al4SiC4 composition had a relative density of 30.0% and a bulk density of 0.91 g / cm 3 The particle size distribution span in the unpulverized state was impossible to measure. The crushability was extremely poor, rated D (solidification of the Al4SiC4 composition was observed). The above results are summarized in Table 1.

[0051] [Table 1]

[0052] The Al4SiC4 compositions obtained in Examples 1 to 6 had a relative density of 20% or less and good crushability, and the Al4SiC4 compositions could be taken out simply by turning over the carbon crucible. In addition, the particle size distribution span in the uncrushed state was 1.5 or less, and the Al4SiC4 compositions could be used as functional additives for carbon-containing refractories without being crushed by a crusher.

[0053] On the other hand, the Al4SiC4 composition obtained in Comparative Example 1 had a relative density exceeding 30%, and solidification of the Al4SiC4 composition was observed. The Al4SiC4 composition could not be taken out by simply turning the carbon crucible upside down, and could not be taken out unless the Al4SiC4 composition was sufficiently crushed. In addition, unless it was crushed by a crusher, it could not be used as a functional additive for carbon-containing refractories.

Claims

1. A raw material including an aluminum source, a silicon source, and a carbon source is mixed, and the mixed raw material is loaded into a crucible and fired under an inert gas atmosphere to produce Al. 4 SiC 4 1. A method of making a composition comprising: Adding activated carbon as part of the carbon source; The amount of the activated carbon added is 0.5 mass% to 40 mass% based on the carbon source. 4 SiC 4 Method for producing the composition.

2. The Al according to claim 1, characterized in that the firing is carried out at a temperature of 1650 to 1900° C. for 1 to 10 hours in an argon atmosphere. 4 SiC 4 Method for producing the composition.

3. The Al4SiC4 composition is Al 4 SiC 4 Aluminum particles agglomerated into clumps 4 SiC 4 1. A composition comprising: The Al 4 SiC 4 The relative density of the composition is Al 4 SiC 4 3. The method for producing an Al 4 SiC 4 composition according to claim 1, wherein the Al 4 SiC 4 composition has a density of 10% to 20% of the theoretical density of the Al 4 SiC 4 composition.

4. The Al 4 SiC 4 The composition was crushed without using a grinder and the particle size distribution on a volume basis was measured. The particle size distribution span (D) is calculated by dividing the difference between the cumulative 90% particle size and the cumulative 10% particle size by the cumulative 50% particle size. 90 -D 10 ) / D 50 The method for producing an Al 4 SiC 4 composition according to claim 3, wherein is 1.0 to 1.5.

Citation Information

Patent Citations

  • Microwave absorbing composition, microwave absorbing body and microwave heating body

    WO2020230707A1